Representações sociais do consumo de carne, Belo Horizonte - MG - 2009 - Guilherme Santiago de Barros (2010)
Feeding is modeled by culture, being full of symbolisms. It is certainly not restricted to a biological phenomena. The goal of the present dissertation was to identify social representations of meat consumption in Belo Horizonte, Minas Gerais, through qualitative methodology. Semi-structured interviews were conducted with 34 Belo Horizonte Central Market goers and analyzed based on the content analyze technique. It was verified that the taste for meat is mainly represented as a cultural construction and also that meat takes a central part onmeals sometimes being used as an element of social cohesion. Although some people regularly adopt the absence of meat during the period of lent this observance showed to be based only on tradition and Catholic Church norm. It was observed that in several occasions red meat detained exclusively in itself the meaning of meat. There were several representations towards health, being meat consumption represented as being healthy or not healthy depending on thecircumstance. Furthermore, when costs were approached, meat transited from a necessary to an optional item. Meat was strongly identified as a source of protein and white meat was considered healthier than red meat. Pork meat was represented as fat and as a potentialdisease carrier. It could be verified that in general social representations of meat consumption are independent of the representations of production animals. Obtained results may be useful to meat industry as well as to non-consuming defenders, opening the doors to research production with more specific side views. Its aim would be in the deepening of social representations study on particular themes that are meat consumption related.